Tingkat stres akademik pada mahasiswa tahun pertama - Saputra, Micho Triana (Maliki Interdisciplinary Journal, 2026)
First-year students are in an important transition period that often triggers academic stress due to increased academic demands, adjustment to a new environment, and changes in learning patterns. Research shows that more than half of new students experience academic stress and are still struggling to develop appropriate coping strategies to deal with academic challenges. Workload, time constraints, learning interactions, and academic difficulties are the dominant factors that increase the psychological pressure on new students. On the other hand, appropriate interventions such as religious coping training have been shown to significantly help reduce stress levels and improve adaptability in the early stages of college. Therefore, higher education institutions need to provide ongoing support through counseling services, self-development programs, and value-based approaches to promote academic success and student well-being